Effects of workload on 3D joint moments in cycling and their implications for injury prevention - Martín-Sosa, Ezequiel; Mayo, Juana; Ojeda, Joaquín (Frontiers in Bioengineering and Biotechnology, 2025)
Background and IntroductionSeveral studies have been published in the literature analysing the effect of workload on joint moments during pedalling. Most of these studies focus on a single plane, mainly the sagittal plane, or on one joint (the knee). In this work a workload effect analysis is proposed on the three main joints of the lower body and on the three anatomical planes. Usually, this type of study has been carried out using 0D metrics such as the maximum or the variable range. In this work the analysis has been extended by complementing it with a statistical parametric mapping analysis.MethodologyTen participants pedalling at 90 rpm and three pedal powers (170, 240 and 310 W) were analysed.ResultsThe results obtained show that pedalling power affects the moments in the three joints and in the three anatomical planes.DiscussionAnalysis of the common causes of the main overload injuries that occur in cycling suggests that a three-dimensional analysis of the joint moments of the three main joints of the lower limb, including 0D and 1D data, is useful for the prevention of these injuries.